Sensory Evaluation Of Ice Cream With Chicken Stock As Stabilizer (Journal of Namibian Studies : History Politics Culture, 2023)
The core intent of this study was to assess the sensory evaluation of ice cream with chicken stock as stabilizer in terms of appearance, aroma, taste, and texture. This study employed the experimental design using the 4-point Hedonic Scale conducted in Tagbilaran City, Baclayon, Panglao, Bohol and Bohol Island State University-Main Campus. There were 375 respondents in the study. The respondents were ice cream makers, ice cream consumers, residents and non-residents of Tagbilaran City, Baclayon, and Panglao, Bohol. Food technology teachers and students, BHRST/BSHM Students, MATVE/MSIT major in food technology masteral students, tourists, food business operators, and food business personnel during the academic year 2018-2019. To determine the respondents’ preference on sensory evaluation and significant difference in the degree of likeness. The data gathered were tabulated using the Weighted Mean. The findings revealed that the shelf-life of ice creams with chicken stock stabilizer lasted for 11th weeks under freezing condition with ice crystals were very apparent in the texture of ice cream,  The ice cream with chicken stock stabilizer were rated “Like Very Much” by the respondents’ preference on liking level with the AWM of 3.57.